2015
DOI: 10.1103/physrevc.92.024315
|View full text |Cite
|
Sign up to set email alerts
|

Triplet energy differences and the low lying structure ofGa62

Abstract: Background: Triplet energy differences (TED) can be studied to yield information on isospin-non-conserving interactions in nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…1. The yrast sequence up to the 17 + state at 9976 keV and the off-yrast part between 2 and 5 MeV excitation energy was reported previously [4][5][6]9,10], the latter in fact more comprehensively. This is readily understood in terms of anticipated entry-state distributions, which are shifted to on average higher excitation energies and larger angular momenta for the present data set.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1. The yrast sequence up to the 17 + state at 9976 keV and the off-yrast part between 2 and 5 MeV excitation energy was reported previously [4][5][6]9,10], the latter in fact more comprehensively. This is readily understood in terms of anticipated entry-state distributions, which are shifted to on average higher excitation energies and larger angular momenta for the present data set.…”
Section: Resultssupporting
confidence: 64%
“…[1][2][3] and references therein). Triplet energy differences along the mass A = 62 isobars 62 Ge, 62 Ga, and 62 Zn have been studied, most recently by two-nucleon knockout [4]. This study provided evidence for the relevant T = 1, I π = 2 + state at 977 keV in 62 Ga, improving upon the results of Ref.…”
Section: Introductionsupporting
confidence: 66%
“…4(c) two TED values for the 2 + state are shown, where the two possible candidates described above have been used for 62 Ga. We cannot yet distinguish experimentally between these possibilities, so we simply note that one of these (the TED based on the 977 keV state from Ref. [24]) matches well with the calculations, and the other does not. As with other mass regions, the TED calculation provides a good agreement with the data only when the INC interaction is included.…”
Section: Comparison Of Experimental and Theoretical Triplet Energmentioning
confidence: 80%
“…An I = 2 state at 1015 keV, first observed by Rudolph et al [23], has been identified as the T = 12 + state on the basis of its similarity to the energy of the analog states in the other members of the multiplet. However, Henry et al [24] subsequently identified a state at 977 keV which they suggested as an alternative candidate for the T = 12 + state, on the basis of the knockout methodology used in that work. In Fig.…”
Section: Comparison Of Experimental and Theoretical Triplet Energmentioning
confidence: 99%
“…Naturally, the Coulomb force will break the degeneracy, although the underlying wave functions are expected to retain their isospin symmetry. A significant body of work has built up in recent years examining the difference in excitation energies between mirror pairs and complete T = 1 isobaric triplets -see, for example, references [12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. These studies, which have involved a shell-model interpretation, have shown that the electromagnetic effects within the shell-model cannot account alone for the energy differences, suggesting that other effective isospin-symmetry-breaking interactions are missing from the models -see [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%